2019
DOI: 10.1002/hed.25954
|View full text |Cite
|
Sign up to set email alerts
|

Young and elderly oral squamous cell carcinoma patients present similar angiogenic profile and predominance of M2 macrophages: Comparative immunohistochemical study

Abstract: Background M2 macrophages are often detected in oral squamous cell carcinoma (OSCC), which, influenced by hypoxic conditions, appear to have high angiogenesis‐inducing capacity. However, the effects of immunosenescence on tumor‐associated macrophages (TAMs) and angiogenesis in OSCC are unknown. Methods Fifty‐seven OSCCs were divided into 3 groups (I: <40 years [n = 17]; II: 40‐65 years [n = 20]; III: >65 years [n = 20]). Immunohistochemistry for CD68 and CD163 (TAMs), and CD34 and D2‐40 for microvessel density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…A worldwide increasing trend in the incidence of OSCC in young adults has been observed in the last decades, although the exact incidence is still uncertain (Borba Ribeiro et al., 2019). Moreover, the cut‐offs reported in the literature defining the “young age” range from 30 to 45 years, highlighting the lack of standardization (de Morais et al., 2017; Oliver et al., 2019; Teixeira et al., 2019). Besides, the role of tobacco and alcohol consumption in the development of OSCC in young adults is still debated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A worldwide increasing trend in the incidence of OSCC in young adults has been observed in the last decades, although the exact incidence is still uncertain (Borba Ribeiro et al., 2019). Moreover, the cut‐offs reported in the literature defining the “young age” range from 30 to 45 years, highlighting the lack of standardization (de Morais et al., 2017; Oliver et al., 2019; Teixeira et al., 2019). Besides, the role of tobacco and alcohol consumption in the development of OSCC in young adults is still debated.…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis is related to the ability of cancer cells to avoid destruction from the host immune system (Chen & Mellman, 2017). Indeed, recent studies have increasingly shown that tumour immune microenvironment plays a critical role in cancer progression, although significant results in young OSCC patients has not yet emerged (Huang et al., 2019; Ryu et al., 2019; Teixeira et al., 2019; Vincent‐Chong et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the preceding, published case series reveals several notable differences in their methodology. These studies often utilized different age thresholds for defining “young.” Age distribution of patients in the presented articles varied, individuals considered young, were those aged ≤30 years (0.8%),[ 3 ] ≤40 years (90%),[ 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 ] and ≤45 years (6.7%). [ 21 22 23 24 25 ] The majority of the studies (nearly 17 studies) classified individuals under 40 years as young.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the country of study, China carried out five works,[ 3 4 7 16 20 ] followed by the United States (four works),[ 15 21 24 26 ] Brazil (three works),[ 10 17 19 ] Pakistan, India, and Korea (two works). [ 8 12 13 14 23 25 ] The remaining works were single reported studies in various countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation